IMPLICATIONS OF OMNIBUS LAW ON JOB CREATION TOWARDS REGULATIONS IN DECENTRALIZATION PERSPECTIVE - Yulia Neta; Malicia Evendia; Ade Arif Firmansyah (Universitas Lampung, 2022)
The discussion about omnibus law in the formation of laws and regulations has become a continuing discourse to this day, this is because omnibus law has been implemented in Indonesia through the work copyright law contained in Law Number 11 of 2020 concerning Job Creation. In its development, through the Constitutional Court Decision Number 91/PUU-XVIII/2020 on the Formal Review of Law Number 11 of 2020 concerning Job Creation, it is stated that the Job Creation Act is conditional. However, on one hand, the Instruction of the Minister of Home Affairs Number 68 of 2021 regarding the Follow-up to the Decision of the Constitutional Court Number 91/PUU-XVIII/2020 becomes a dilemma because in Indonesia regions must continue to follow the Job Creation Act and make adjustments to regional regulations on the follow-up to the existing law. The content material in the work copyright law is so diverse that it consists of eleven clusters and has changed, deleted and/or stipulated new arrangements for several provisions regulated in various laws, which have implications for the laws and regulations below them, including the regulations. On the other hand, some local government authorities have also experienced a shift through the law. The implications of the omnibus law regarding job creation on regional regulations include the deregulation of various regional regulations as a delegation of norms from higher regulations, and the responsibility of regional governments in harmonizing and synchronizing regional regulations in an effort to optimally implement autonomy and co-administration tasks.